Economic potential of enterprise in conditions of knowledge economy - Кісь, Г. Р. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
In the present article basic approaches to interpret the category of "economic potential" are considered. The author’s approach to identify the target concept, which is based on the necessity to consider intelligence as the main factor of industrial management development in conditions of cognitive economy is demonstrated. It is stated that intellectual potential is not only a part of enterprise economic potential but is also an inseparable component of all its types. An updated structure of economic potential is suggested, taking into account working elements of intellectual potential performance.